Zinc finger motif-1 antagonizes PDGF-BB-induced growth and dedifferentiation of vascular smooth muscle cells - Cattaruzza, Marco; Nogoy, Nicole Alberta; Wójtowicz, Agnieszka; Hecker, Markus (The FASEB journal, 2012)
Zinc finger motif-1 (ZFM1) represses proinflammatory gene expression in vascular smooth muscle cells (SMCs) at a global level and thus may also be involved in the attenuation of growth factor-induced phenotype changes in these cells. Using human primary cultured thymus vein SMCs, we have investigated the molecular mechanism by which a potent SMC mitogen, platelet-derived growth factor-BB (PDGF-BB), causes a rapid decrease in ZFM1 expression in a concentration-dependent manner and consequences thereof. Reporter gene analyses and chromatin immunoprecipitation showed that PDGF-BB-induced ZFM1 repression occurs at the level of transcription through replacement of the activating transcription factor Sp1 by Egr-1. The subsequent drop in ZFM1 abundance disinhibits SMC proliferation, migration, and synthetic gene expression in a concerted manner. Stabilizing ZFM1 levels in a PDGF-BB-independent way with a GFP-ZFM1 expression construct or by using Egr-1-specific decoy oligonucleotides abrogates all PDGF-BB effects. Conversely, siRNA-mediated knockdown of ZFM1 alone not only increases the sensitivity of SMCs for PDGF-BB, but even mimics PDGF-BB-induced proliferation and gene expression. Our findings suggest that ZFM1 is an important factor for the stabilization of a contractile SMC phenotype under basal or mildly activating conditions and that, as a prerequisite for efficient action, PDGF-BB must repress ZFM1 expression to alter the SMC phenotype.—Cattaruzza, M., Nogoy, N., Wojtowicz, A., Hecker, M. Zinc finger motif-1 antagonizes PDGF-BB-induced growth and dedifferentiation of vascular smooth muscle cells.
Gesehen am 03.05.2018